Confounding of Big Five Personality Assessments in Emotional Disorders by Comorbidity and Current Disorder. Issue 4 (28th September 2012) - Spinhoven, Philip; van der Does, Willem; Ormel, Johan; Zitman, Frans G.; Penninx, Brenda WJH
Abstract: Foremost cross‐sectional studies of personality in common mental disorders show similar Big Five trait profiles [i.e. high neuroticism (N), low conscientiousness (C) and low extraversion (E)]. It remains undecided whether this lack of distinct personality profiles is partly due to comorbidity among disorders or contamination by current state. Using data from the Netherlands Study of Depression and Anxiety, we investigated 1046 participants with panic disorder (PD), social anxiety disorder (SAD) and/or major depressive disorder (MDD) and 474 healthy controls. Personality traits at baseline and two‐year follow‐up were assessed with the NEO‐Five Factor Inventory. The Composite International Diagnostic Interview was used to determine the presence of emotional disorders at baseline and at two‐year follow‐up; the Life Chart Interview determined symptom severity in the month prior to baseline and during follow‐up. By analysing pure cases and investigating the effects in remitted cases, PD participants were found to be higher in N, but not lower in E and C than controls. Pure PD participants were also lower in N and higher in E than SAD and MDD participants. Both SAD and MDD participants were characterized by high levels of N and low levels of E, irrespective of comorbidity or current disorder state. Future studies should be more attentive to confounding of personality profiles by comorbidity and state effects. Copyright © 2012 John Wiley & Sons, Ltd.